2023
DOI: 10.3390/e25030498
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Rectification and Amplification in Interacting Quantum-Dot Circuit-Quantum-Electrodynamics Systems

Abstract: Thermoelectric rectification and amplification were investigated in an interacting quantum-dot circuit-quantum-electrodynamics system. By applying the Keldysh nonequilibrium Green’s function approach, we studied the elastic (energy-conserving) and inelastic (energy-nonconserving) transport through a cavity-coupled quantum dot under the voltage biases in a wide spectrum of electron–electron and electron–photon interactions. While significant charge and Peltier rectification effects were found for strong light–m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…[31], proposing that thermal transistor effects could occur in the linear-transport regime, particularly when dominated by phonon-assisted inelastic transport. In our subsequent work, [7,33] we further demonstrated the existence of linear thermal transistor effects in circuit-quantum-electrodynamics systems across a wide range of QD energies and light-matter interactions. Furthermore, we showed that thermal transistor effects can manifest even without these conditions in Brownian thermal transistors.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…[31], proposing that thermal transistor effects could occur in the linear-transport regime, particularly when dominated by phonon-assisted inelastic transport. In our subsequent work, [7,33] we further demonstrated the existence of linear thermal transistor effects in circuit-quantum-electrodynamics systems across a wide range of QD energies and light-matter interactions. Furthermore, we showed that thermal transistor effects can manifest even without these conditions in Brownian thermal transistors.…”
mentioning
confidence: 77%
“…[1][2][3] Phonon-thermoelectric transport stands at the intersection of mesoscopic physics and opens quantum systems, exploring topics such as thermoelectric energy conversion in phonon-thermoelectric devices [4,5] and quantum dot (QD) circuit-quantum-electrodynamics. [6][7][8] Recently, various quantum phenomena based on QDs subjected to voltage bias and temperature gradients have been explored, revealing stressing the influence of quantum coherence on electron and phonon transport. [9][10][11][12][13][14][15] Coherence offers a promising viewpoint for investigating non-equilibrium open quantum systems, providing valuable insights for both theoretical foundations and practical applications.…”
mentioning
confidence: 99%